Residual futures : the urban ecologies of literary and visual media of 1960s and 1970s Japan - Prichard, Franz, 1976- (Studies of the Weatherhead East Asian Institute, Columbia University., 2019)
"The first book-length study of the ways in which filmmakers, writers, photographers, and other artists came to grips with Japan's urbanization and integration into the U.S. geopolitical system in the 1960s and 70s. The works Prichard discusses in this book tell a story of radical criticism, thought, and cultural practice at a time of rapid change in Japan and across East Asia. In the first chapter, Prichard examines the documentary filmmaker Tsuchimoto Noriaki's engagement with the dispossession effected by the material remaking of Tokyo ahead of the 1964 Olympics. Chapter two undertakes a "topological analysis" of Abe Kobo's late-1960s writings, focusing on the themes of anonymity and urban sociality. In the last three chapters, Prichard explores the critical and photographic work of Nakahira Takuma, who elaborates, along with other critics with whom he enters into dialogue, what Prichard calls "a radical discourse of landscape"--